Antidepressant tapering strips to help people come off medication more safely. Issue 2 (3rd April 2018) - Groot, Peter C.; van Os, Jim
ABSTRACT: Antidepressants are commonly prescribed for many mental disorders, including psychosis. Withdrawal effects, resulting from inappropriately short duration of tapering or lack of flexibility in prescribing gradual reduction, are common. An observational study was conducted of the use of "tapering strips", which allow gradual dosage reduction and minimise the potential for withdrawal effects. A tapering strip consists of antidepressant medication, packaged in a roll of small daily pouches, each with the same or slightly lower dose than the one before it. Strips come in series covering 28 days. Of 1194 users of tapering strips, 895 (75%) wished to discontinue their antidepressant medication. In these 895, median length of antidepressant use was 2–5 years (IQR: 1–2 years– > 10 years). Nearly two-thirds (62%) had unsuccessfully attempted withdrawal before (median = 2 times before, IQR 1–3). Almost all of these (97%) had experienced some degree of withdrawal, with 49% experiencing severe withdrawal (7 on a scale of 1–7, IQR 6–7). The most common medications were paroxetine ( n = 423, 47%) and venlafaxine ( n = 386, 43%). Of the 895 wishing to discontinue, 636 (71%) succeeded in tapering their antidepressant medication completely, using a median of 2 tapering strips (IQR 1–3) over a median of 56 days (IQR = 28–84). Tapering strips represent a simple and effective method of achieving a gradual dosage reduction.